The potential of GPS Precise Point Positioning method for point displacement monitoring: A case study. (September 2016) - Yigit, Cemal Ozer; Coskun, M. Zeki; Yavasoglu, Hakan; Arslan, Abdullah; Kalkan, Yunus
Abstract: Relative/network GPS/GNSS (Global Positioning System/Global Navigation Satellite System) positioning has been widely used to precisely measure both structural and crustal deformation monitoring for more than two decades ago. In recent years, interest has increased for PPP (Precise Point Positioning) method due to its capability to generate positioning solutions as accurate as relative GPS/GNSS positioning. The main aim of this paper is to investigate the efficacy and performance of PPP method for point displacement monitoring considering long to short (24 h, 12 h, 6 h, 3 h) observation period. For this purpose, it was developed high accuracy displacement simulator apparatus, which is able to move accurately over a small distance in one direction and horizontal plane. Ten simulated displacement movement tests (2, 3, 6, 11, 15, 21, 30, 40, 50 and 60 mm) were conducted. Eleven 24 h GPS datasets, including the reference epoch and ten simulated displacement cases, were collected. Daily datasets were split into 12 h, 6 h and 3 h subsets in order to investigate the impact of data length on estimated displacement. All datasets were processed by both PPP method and relative GPS method. Then, PPP-estimated and relative GPS-estimated displacements were compared to actual displacements and also statistical significance test performed to see which displacement amount can be detectable using both methods. The results show that PPP method based on 24 h observation period can be determine up to 1.5 cm horizontal displacement.